Manajemen pelayanan donasi online di Laznas Baitul Mall Hidayatullah Provinsi Sumatera Utara - Halawa, Irwan; Ritonga, Hasnun Jauhari (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study analyzes the management of online donation services at LAZNAS Baitul Maal Hidayatullah (BMH) in North Sumatra Province. In the digital era, BMH has developed a donation platform aimed at enhancing transparency and accountability in the management of zakat, infaq, and charity. The research method employed is qualitative, with data collection through in-depth interviews with BMH administrators, participatory observation of the donation process, and document analysis related to financial reports and operational procedures. The findings indicate that this online donation system not only facilitates the donation process for donors but also increases their trust through clear and accessible reports on fund utilization. Additionally, the platform allows for real-time tracking and management of contributions, contributing to the efficient distribution of aid to the underprivileged. The study also finds that feedback from donors is crucial in enhancing the transparency and accountability of the institution's financial management. Thus, BMH can continue to improve and innovate its online donation system, reaching more muzakki and increasing the social impact of its programs. In conclusion, the application of technology in donation management at BMH significantly contributes to the development of better and more responsive zakat management to meet community needs.